2013
DOI: 10.5322/jes.2013.22.1.59
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Concentrations of Heavy Metal in Blood and Urine of Local Area in Korea

Abstract: The purpose of this study is to assess the effects of heavy metal concentrations in the blood and urine of the general population. This research had been conducted from April to December 2008, studying 545 residents of Daejeon and Chungcheong Province. Through the concentrations of heavy metals(Pb, Cd, Hg, As, Mn) in the biota samples and questionnaires, the residents heavy metal exposure level and the influential factors according to personal characteristics or lifestyle were evaluated. As to the heavy metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the present study, we observed a trend for higher urinary Cd concentration with older age, which is consistent with previous studies. One study investigating the general Korean population found increasing urinary Cd levels with older age [ 46 ], and another study of residents in parts of Korea without any obvious source of contamination showed that older age was associated with significantly increased urinary Cd concentration [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed a trend for higher urinary Cd concentration with older age, which is consistent with previous studies. One study investigating the general Korean population found increasing urinary Cd levels with older age [ 46 ], and another study of residents in parts of Korea without any obvious source of contamination showed that older age was associated with significantly increased urinary Cd concentration [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Males had higher B-Pb levels than those of females in German human biomonitoring commission research [ 24 ]. As age increases, blood concentrations of heavy metals increase, particularly in those between 40–59 years old, who have recorded the highest concentration of 2.56 µg/dL [ 2 , 25 ]. The age difference reflects the difference between the amount of activity and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The South Korean government has led the development of petrochemical, non-ferrous metal, shipbuilding, automotive industries, and urbanization since the 1960s, according to heavy chemical industry development policies. Thus, the type and amount of harmful substances entering the environment has increased rapidly, and the chances for exposure have increased [ 2 , 3 , 4 ]. Environmental policies are no longer sufficient to prevent pollution and protect the public, which deserves safe environmental quality [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations